2015
DOI: 10.3109/10799893.2015.1015739
|View full text |Cite
|
Sign up to set email alerts
|

Mapping inhibitor response to the in-frame deletions, insertions and duplications of epidermal growth factor receptor (EGFR) in non-small cell lung cancer

Abstract: Human epidermal growth factor receptor (EGFR) has become a well-established target for the treatment of non-small cell lung cancer (NSCLC). However, a large number of in-frame deletion, insertion and duplication mutations in the EGFR tyrosine kinase (TK) domain have been observed to alter drug response to such a kinase target. Thus, a systematic investigation of the intermolecular interactions between the clinical small-molecule agents and various EGFR in-frame mutants would help to establish a complete pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…24 Exon 19 insertions, L747F and P733L, have both been reported as sensitizing rare exon 19 mutations 20 and several rare mutations in exon 19 have been reported as resistance mutations, including D761Y, E746V, and L747S, showing the varied responses that different point mutations in one exon can elicit. 20 The L747F mutation may confer sensitivity by inhibiting the aC helix adopting the inactive position, 25 whereas the D761Y resistance mutation appears to confer resistance by altering the receptor interaction with ATP. 20 In two case studies by Agbarya et al and Chan et al, data from female patients with p.K745_E746insIPVAIK exon 19 insertions were reported, and in both cases the patients responded to EGFR TKI treatment.…”
Section: Exon 19 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Exon 19 insertions, L747F and P733L, have both been reported as sensitizing rare exon 19 mutations 20 and several rare mutations in exon 19 have been reported as resistance mutations, including D761Y, E746V, and L747S, showing the varied responses that different point mutations in one exon can elicit. 20 The L747F mutation may confer sensitivity by inhibiting the aC helix adopting the inactive position, 25 whereas the D761Y resistance mutation appears to confer resistance by altering the receptor interaction with ATP. 20 In two case studies by Agbarya et al and Chan et al, data from female patients with p.K745_E746insIPVAIK exon 19 insertions were reported, and in both cases the patients responded to EGFR TKI treatment.…”
Section: Exon 19 Mutationsmentioning
confidence: 99%
“…Exon 20 mutations may function by altering the kinase domain conformation. 20 Although many exon 20 mutations have been reported as conferring resistance to erlotinib by altering the P-loop and thus reducing the ATP-binding pocket, 25 a retrospective study by Naidoo et al reported a V769_770insASV insertion that resulted in a PFS of 19.8 months (z602 days) and an OS of 24 months (z730 days), and a patient with a D770_N771insGT insertion achieving an OS of 55 months (z1674 days), thus demonstrating the variability of rare mutation effects. 33 Another retrospective study analyzed 1086 patients for EGFR mutations and identified 27 patients (2.5%) with exon 20 insertions, with the most common variant being V769_D770insASV.…”
Section: Exon 19 Mutationsmentioning
confidence: 99%
“…In vitro studies also show that these insertions lead to a considerable smaller ATP-binding pocket, thus decreasing the affinity for TKIs and explaining the inherent resistance. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the proposed DNA sensor based on MWCNTs and TSPP probably exhibits a high sensitivity for all previously ascribed reasons such as the high specific surface of CNTs, the short distance between porphyrin and CNTs that increases electron transfer [ 19 , 23 ], and especially different attractions or repulsions occurring among CNTs, ssDNA/dsDNA and anionic porphyrin, which produce synergetic effects to amplify the impedance difference to be big enough for target DNA detection without any label. As can be seen from Table 3 , compared with some biosensors for the detection of DNA specific to genes from the same family of tyrosine kinase receptor [ 43 , 44 , 45 , 46 , 47 ], such as HER2 (also known as ERBB2 or c-erbB-2) and HER1 (also known as EGFR [ 48 ]), our work presents an excellent sensing platform that can be constructed in a quite simple way with good sensitivity and a wide dynamic range ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%